ALIH FUNGSI LAHAN PERTANIAN MEBJADI LAHAN PERIKANAN DI NAGARI TARUANG-TARUANG KECAMATAN RAO KABUPATEN PASAMAN TIMUR - gustia, Vivi; Juita, Erna; Prarikeslan, Widya (Pendidikan Geografi, 2013)
This research purposes to get data and information such as : 1) income society 2) knowledge 3) land manufacture before and after funetion change of land. Kind of this research is descriptive and become of populalation this research is the village of doing function change of land in Nagari Taruang-taruang Kecamatan Rao Kabupaten Pasaman Timur consist of some the villages such as: Mudiak Tampang, Sawah Ateh, Soriak. Example of district take in toward methode purpose sampling is the district more many doing function change of land is kampuang Sawah Ateh and kampuang Soriak. Example of respondence take in totally sampling as big as 116 respondance totally KK that doing function change of land. Produce this research found : 1) Income farmer society before function change of land in medium is about Rp. 2.000.000Â  â Rp. 3.499.000 like53 people (45,69%). White after function change of land become fisheries land included high is â¥ Rp. 5.500.000 â Rp. 6.500.000 like 73 people (62,93%). 2) knowledge of society before and after function change of land is not known about agriculture land and fishery is 84 people (72,41%). Best before and after function change of land the society harvest of produce agriculture and fishery two times in one years is 116 people (100%). 3) Before function change of land the largeagriculture lan society 15 â¥ 2 Ha like 58 people (50%)Â  and while after function change of landthe large lan of society 1 Ha is 53 people (45,69).